Criminal Discount Factors and Deterrence - Giovanni Mastrobuoni; David A. Rivers (Institute for the Study of Labor (IZA), 2016)
The trade-off between the immediate returns from committing a crime and the future costs of punishment depends on an offender's time discounting. We exploit quasi-experimental variation in sentence length generated by a large collective pardon in Italy and provide non-parametric evidence on the extent of discounting from the raw data on recidivism and sentence length. Using a discrete-choice model of recidivism, we estimate an average annual discount factor of 0.74, although there is heterogeneity based on age, education, crime type, and nationality. Our estimates imply that the majority of deterrence is derived from the first few years in prison.
Keywords: D9; K4; 330; discounting; deterrence; collective pardon; recidivism